Storytelling in the Defense Sector - Nizheiko, Kostyantin; Lendel, Oleksandra (Social Development and Security, 2025)
Purpose. To identify the communicative and informational-psychological aspects of storytelling as a tool of influence in the military-industrial sphere and national security. Findings. A general definition of storytelling, its functions, and role in forming an emotional connection between the audience and the communicator are provided. Particular attention is paid to the analysis of defense activities in the context of modern information warfare, where storytelling is used as an effective means of psychological influence, mobilization of support, and formation of a positive image of military structures. Current trends in the use of storytelling in military communications, particularly in strategic communications, information campaigns, and influence operations, are outlined. Typical themes of military narratives are explored: heroism, sacrifice, brotherhood, struggle for independence, and defense of values. The features of military storytelling are identified, such as emotional intensity, appeal to national identity, visual and audio expressiveness, and adaptation to various platforms (social networks, video, blogs, documentary formats, etc.). Originality. The study presents in a systematized storytelling as a comprehensive communication tool in the defense sector, combining psychological, marketing, and strategic dimensions. It proposes a structured mechanism for using storytelling to influence public opinion, government decisions, and the positioning of defense industry products in the international environment. The main steps for the practical implementation of storytelling in the strategies of Ukrainian defense sector companies are substantiated.